Penerapan ISO 14001:2015 pada Institusi Pendidikan Pondok Pesantren: (Studi Kasus di Pondok Pesantren X Yogyakarta) - A. Hadian Pratama Hamzah; Abdul Hamid; Nurhasanah Nurhasanah (Universitas Nusantara PGRI Kediri, 2023)
As an educational institution with a high number of civitas and activities, activities at Islamic boarding schools have the potential to have a large impact on the environment. However, the term environmental management system is still not very popular within the Islamic boarding school environment. Through mixed descriptive analysis (qualitative-qualitative), this paper attempts to explain the gap between the implementation of an environmental management system at the Al Jauhar Islamic Boarding School and ISO 14001:2015. The results of this study indicate that the implementation of the environmental management system at the Al Jauhar Islamic Boarding School is still not optimal. This condition is indicated by the few criteria that comply with ISO 14001:2015. These findings suggest the importance of the involvement of the government and academics in providing an understanding regarding the importance of an environmental management system to be implemented in an educational institution with high activity such as Islamic boarding schools. The information conveyed regarding environmental management should not have implications for increasing the financial burden for Islamic boarding schools, but instead support increasing economic efficiency so that managers are willing to voluntarily implement ISO 14001:2015.